Anoa, dwarf buffalo from Sulawesi, Indonesia: Identification based on DNA barcode - DWI SENDI PRIYONO; DEDY D. SOLIHIN; ACHMAD FARAJALLAH; DIAH IRAWATI DWI ARINI (Biodiversitas Journal of Biological Diversity, 2018)
Priyono DS, Solihin DD, Farajallah A, Arini DID. 2018. Anoa, dwarf buffalo from Sulawesi, Indonesia: Identification based on DNA barcode. Biodiversitas 19: 1985-1992. Anoa is an endangered endemic species in Sulawesi. The controversial issue of anoa conservation until now is the taxonomic status of lowland and mountain anoa. This study aims to test the ability of DNA barcoding techniques to identify the taxonomy between mountain anoa and lowland anoa. A 681bp fragment of cytochrome oxidase subunit 1 (COI) gene was obtained and used to solve the molecular taxonomic problem and to resolve the phylogenetic relationships of the two types of anoa. Our results showed that the DNA barcode is useful in assigning the taxonomic position of anoa. In the phylogenetic tree, we found that the two types of anoa were in separate clades. We also found that based on the Kimura-2 parameter (K2P), the genetic distance between the two types of anoa showed higher values (3.4%) than the threshold of the separating species level. We, therefore, proposed that the binomial nomenclature for both types of lowland and mountain anoa are respectively Bubalus depressicornis and Bubalus quarlesi. We suggest that the use of DNA barcode techniques in anoa taxonomic studies and their implementation will be useful in conservation management